Application of the AHP Method for the Selection of Majors in Higher Education through the SNBP Route - Saputri, Zona; Gamal, M. D. H.; Hasbiyati, Ihda (Universitas Pahlawan Tuanku Tambusai, 2025)
SNBP is one of the entry points in state university entrance selection system which is very popular with students because selection for university entrance is carried out only based on based on the results of academic achievement tracking through report cards and students' academic and non-academic portfolios. MAN 1 Siak is one of the madrasas that registers its students through the SNBP entry. When SNBP registration opens, the role of guidance and counseling teachers is really needed to help students in choosing the right major. The aim of this research is to make it easier for guidance and counseling teachers to create a decision support system that can provide recommendations for major selection to students effectively and efficiently. The method used is the analytical hierarchy process (AHP) method. AHP is a decision making method with a systems approach, where decision makers try to understand a system condition and help make predictions in making decisions. Using the AHP method, the priorities for selecting majors in higher education via the SNBP route are education(0.2912), economics(0.2447), computers(0.2168), law(0.2007), and medicine(0.0466).